Clinical and microbiological features of invasive nontyphoidal Salmonella associated with HIV-infected patients, Gauteng Province, South Africa. Issue 13 (March 2017) - Keddy, Karen H.; Musekiwa, Alfred; Sooka, Arvinda; Karstaedt, Alan; Nana, Trusha; Seetharam, Sharona; Nchabaleng, Maphoshane; Lekalakala, Ruth; Angulo, Frederick J.; Klugman, Keith P.
Abstract : Abstract: The aim of this study was to define factors associated with HIV-infected versus uninfected patients with invasive nontyphoidal Salmonella (iNTS) and factors associated with mortality, which are inadequately described in Africa. Laboratory-based surveillance for iNTS was undertaken. At selected sentinel sites, clinical data (age, sex, HIV status, severity of illness, and outcome) were collected. Surveillance was conducted in Gauteng, South Africa, from 2003 to 2013. Clinical and microbiological differences between HIV-infected and uninfected patients were defined and risk factors for mortality established. Of 4886 iNTS infections in Gauteng from 2003 to 2013, 3106 (63.5%) were diagnosed at sentinel sites. Among persons with iNTS infections, more HIV-infected persons were aged ≥5 years (χ 2  = 417.6; P  < 0.001) and more HIV-infected children were malnourished (χ 2  = 5.8; P  = 0.02). Although 760 (30.6%) patients died, mortality decreased between 2003 [97/263 (36.9%)] and 2013 [926/120 (21.7%)]. On univariate analysis, mortality was associated with patients aged 25 to 49 years [odds ratio (OR) = 2.2; 95% confidence interval (CI) = 1.7–2.7; P  < 0.001 and ≥50 years (OR = 3.0; 95% CI = 2.2–4.1; P  < 0.001) compared with children < 5 years, HIV-infected patients (OR = 2.4; 95% CI = 1.7–3.4; P  < 0.001), and severe illness (OR = 5.4; 95% CI = 3.6–8.1; P  < 0.001). On multivariate analysis, mortality was associated with patients aged ≥50 years [adjusted OR (AOR) = 3.6, 95% CI = 2.1–6.1, P  < 0.001] and severe illness (AOR = 6.3; 95% CI = 3.8–10.5; P  < 0.001). Mortality due to iNTS in Gauteng remains high primarily due to disease severity. Interventions must be aimed at predisposing conditions, including HIV, other immune-suppressive conditions, and malignancy.